Muhammad Abduh’s Rational Hermeneutics and Its Implications for Islamic Legal Reform - Amir, Ahmad Nabil; Abdul Rahman, Tasnim (Al-Daulah : Journal of Criminal Law and State Administration Law, 2025)
Research Objective: Investigates Muhammad Abduh's rational hermeneutics as a foundation for Islamic legal reform, exploring how his integration of reason ('aql), ethics, and revelation (naql) reconfigures Qur'anic interpretation to revitalize ijtihad and promote justice-aligned legal principles. Research Method: The research employs a qualitative design grounded in hermeneutical analysis and Islamic legal theory. It analyses key verses from Tafsir al-Manar, Tafsir Juz 'Amma, and Risalat al-Tawhid using textual, contextual, and comparative approaches to assess jurisprudential significance. Results: Abduh's tafsir consistently elevates ethical reasoning, public welfare, and maqāṣid al-sharīʿah above rigid textualism. His interpretations of verses concerning religious freedom (2:256), family law (4:3), justice (5:8), and gender equity (33:35) reflect a reformist orientation rooted in moral deliberation. Findings and Implications: The findings reveal a transformative legal paradigm reframing Islamic law as an adaptable, ethically driven system. Abduh's approach supports institutional reform and offers credible alternatives to formalist legal reasoning in addressing pluralism, governance, and human rights. Conclusion: Abduh's rational hermeneutics demonstrates that Islamic legal thought can be renewed through a principled balance of textual fidelity and moral responsiveness, affirming ijtihad's enduring relevance in contemporary legal discourse. Contribution: The study enriches Islamic legal scholarship by offering an analytical model bridging classical jurisprudence and modern ethical challenges, positioning tafsir as a meaningful tool in legal reform. Limitations and Suggestions: The study's limitation lies in its textual focus without assessing practical implementation. Future research should examine the framework's applicability in digital ethics, environmental jurisprudence, and policy-making